Revealing the Impact of Mitochondrial Fitness During Early Neural Development Using Human Brain Organoids - Romero-Morales, Alejandra I.; Gama, Vivian (Frontiers in Molecular Neuroscience, 2022)
The brain is one of the most complex organs in the human body. Centuries of research have shown that it is generated through a finely orchestrated series of events that take place in the first weeks of life up to early adulthood. Mitochondrial homeostasis provides guidance to the intrinsic developmental programs of neuro and corticogenesis, while also being responsive to environmental and intercellular signals. Two- and three-dimensional platforms have become useful tools to interrogate the capacity of cells to generate neuronal and glia progeny in a background of metabolic dysregulation. Here we provide a concise overview of cortical development and the use of pluripotent stem cell models that have contributed to our understanding of mitochondrial and metabolic regulation of early human brain development. We finally discuss the effects of mitochondrial fitness dysregulation seen under stress conditions such as metabolic dysregulation, absence of developmental apoptosis, and hypoxia; and the avenues of research that can be explored with the use of brain organoids.